Beyond the Flow Scholarly Publications During and After the Digital - Walkowski, Niels-OIiver (meson press, 2019)
In the wake of the so-called digital revolution numerous attempts have been made to rethink and redesign what scholarly publications can or should be. Beyond the Flow examines the technologies as well as narratives driving this unfolding transformation. By unpacking the confusion, heterogeneity and uncertainty that is surrounding scholarly publishing today the book asks for how a sustainable post-digital publishing ecology can be imagined.